Nest site selection in sea turtles shows consistencies across the globe in the face of climate change - Holly Stokes (Animal Behaviour, 2024)
Sea turtles face a risk of extinction due to climate change causing warming of nests, which may increase both sex ratio skews, with fewer males being produced, and embryo mortality in nests. In theory, these threats could be mitigated by turtles switching their nest sites to cooler locations on beaches. We assessed nest positioning for green turtles, Chelonia mydas, in the Chagos Archipelago, a major nesting site in the Indian Ocean, and showed that nests were generally in vegetation at the back of the beach, where the risk of sea water inundation was lowest. The relatively few nests on the open beach were on average close to the vegetation. Sand temperatures at nest depths were similar across three beach zones (open sand, edge of vegetation, within the vegetation). Nest positioning was reviewed for 51 studies at 53 sites (including the current study) across the globe and across seven species: green turtles, hawksbills, Eretmochelys imbricata, loggerheads, Caretta caretta, leatherbacks, Dermochelys coriacea, olive ridleys, Lepidochelys olivacea, Kemp's ridleys, Lepidochelys kempii, and flatbacks, Natator depressus. Both in the Chagos Archipelago and across the globe studies show turtles generally tend to crawl a sufficient distance to minimize sea water overwash of nests, which can kill embryos. Hence maximizing embryo survival, rather than considerations of hatchling sex ratios, seems to be the main driver for nest positioning and so we conclude that sea turtles are, generally, unlikely to switch to select cooler beach sites to mitigate climate warming.